Критерии арбитражного эффекта экологического контроля - Уберман, В. И.; Васьковец, Людмила Антоновна (НТУ "ХПИ", 2007)
Уводиться поняття арбітражного ефекту екологічного контролю та пропонується система критеріїв оцінки цього ефекту від дій та рішень при визначенні забруднення земель виробничих майданчиків підприємств. Система критеріїв перевіряється на прикладі контролю виробничого майданчика ВАТ "Тепловозоремонтний завод", м. Полтава, для пріоритетних забруднюючих речовин-нафтопродуктів та свинцю. Критерії охоплюють усі ланки процедури контролю, від визначення еколого-правового статусу об'єкта до оцінки шкоди від забруднення. Критерії призначені для використання у діяльності природокористувачів та органів охорони природи, при еколого-інспекторських перевірках, науково-технічних, екологічних, судових експертизах та арбітражних дослідженнях екологічної безпеки.

The notion of arbitrary effect for environmental checking (inspection) is introduced and the system of criteria for assessing this effect from actions and decisions in finding of polluted soils within sites of industrial enterprises (plants) is proposed. These criteria were verified approved for the example of state inspection on industrial site of JSC "Heat-engine locomotive repairing plant" in Poltava city, for two priority pollutants as lead and oil product contaminants. These criteria describe and include all stages of inspection procedure, from determination of environmental law status for inspected site to possible harm (damage) caused given pollution. Proposed criteria intend for natural-users activity, for environmental inspections, for different kinds of expertise: scientific and engineering, environmental, judicial, and for arbitrary examinations in cases of environmental emergency.
Keywords: охрана окружающей природной среды; природные ресурсы; экологические нирушения; производственные площадки; загрязнения